2019
DOI: 10.1111/jace.16279
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting aqueous alkaline silicates as precursors for sol‐gel optical coatings

Abstract: Alkaline silicates are well-known soluble silica derivatives already widely used for industrial purposes. Nevertheless, their applications for the elaboration of functional optical coatings have largely been discarded by the sol-gel community who mainly focused on alkoxide precursors. The objective of this work is to reconsider the alkaline silicates sol-gel chemistry, targeting optical coatings of a few hundreds of nanometers. The structures of Li + , Na + , and K + silicate coatings are discussed on the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…17 To cope with this issue, a common practice involves rinsing the AR film with water to remove sodium ions from the surface of the film. 18,19 On the other hand, previous work 20,21 has reported that residual sodium ions at the film–glass interface may enhance interfacial reactions through diffusion after annealing and promoting adhesion, which is beneficial for SiO 2 AR film functioning.…”
Section: Introductionmentioning
confidence: 99%
“…17 To cope with this issue, a common practice involves rinsing the AR film with water to remove sodium ions from the surface of the film. 18,19 On the other hand, previous work 20,21 has reported that residual sodium ions at the film–glass interface may enhance interfacial reactions through diffusion after annealing and promoting adhesion, which is beneficial for SiO 2 AR film functioning.…”
Section: Introductionmentioning
confidence: 99%